Exploring the optical, structural, and gamma shielding performance of Dy₂O₃-Doped Li₂O–B₂O₃–Al₂O₃ glass systems - Aljewaw, Osama Bagi; Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Baki, Sharudin Omar; Abdulla, Youssef A.; Tahir, Dahlang; Abdul Karim, Muhammad Khalis (Elsevier Ltd, 2025)
In this study, we synthesized Li₂O–B₂O₃–Al₂O₃ glasses incorporating varying amounts of Dy₂O₃ through the melt-quenching method. The glass formulations followed the composition 23Li₂O + (69 - x)B₂O₃ + 8Al₂O₃ + xDy₂O₃, where x was 0, 1, 1.5, 2, 2.5, and 3 mol%. The glass was found to have an amorphous structure through X-ray diffraction analysis, with Fourier-transform infrared spectroscopy revealing the existence of BO₃ and BO₄ structural units. Mass variation and weight loss rates were evaluated using thermogravimetric analysis and differential thermogravimetry. Optical studies indicated that the direct and indirect bandgap energies were between 3.65–3.76 eV and 2.98–3.29 eV, respectively, as the concentration of Dy₂O₃ increased. The Urbach energy showed a decreasing trend with the higher Dy₂O₃ content, indicating improved structural stability and reduced disorder in the glass network. The Phy-X software was used to determine various radiation attenuation parameters for the selected glass samples for photon energies ranging from 0.015 to 15 MeV. As a result, LBAD-3 showed the optimal performance among the samples. At low photon energy, 0.015–0.05 MeV, LAC values varied from 38.56 to 1.89 cm⁻1. The maximum MAC values at 15 keV were recorded as 15.347 cm2/g for the glass samples LBAD-3. At 15 keV, the smallest HVL values are observed to be 0.017 cm, and the highest values for Zeff were found at a low energy photon range (0.015 MeV) with values of 38.73, while the lowest values were found at 9.650 at 15 MeV for LBAD-3 glasses. There was a notable increase in the buildup factor within the 0.1–10 MeV energy range, with a gradual decrease at higher photon energies. Moreover, the computed ΣR values, with a maximum of 0.104 cm⁻1 for the LBAD-3 sample, highlight its strong potential for fast neutron attenuation. The photon shielding capability of the glass was evaluated using the effective removal cross-section, revealing that the glass containing 3 mol% Dy₂O₃ outperformed the other compositions in photon attenuation. This innovative glass system holds the potential for advancing radiation shielding technologies in the future.